(untitled) (Research, Society and Development, 2021)
Brazil is a country that stands out for its great agricultural activity, as a result, it is one of the countries that most produces agro-industrial waste. It has a prominent position in terms of fruit production. Food, in addition to providing essential nutrients necessary for life, provide bioactive compounds with biological properties known to promote health, such as antioxidant, anticarcinogenic activity of nutrients such as vitamins C, A and E, and phenolic compounds such as flavonoids. The processing of these fruits to produce pulps and juices is responsible for the generation of tons of waste, most of which are disposed of inappropriately, resulting in major environmental problems. As an alternative for the application of the by-products, studies indicate that tropical fruit waste have a high content of phenolic compounds and antioxidant activity. A survey of articles published in journals between the years 2015-2019 was carried out in the Google Scholar, Scielo and Web of Science databases.